Strategic path to enhance the impact of internet broadband on the creative economy in Thailand: An analysis with structural equation model - Pruekruedee S. (Springer Verlag, 2015)
© Springer International Publishing Switzerland 2015. This paper aims at finding the impact of internet broadband on the creative economy in Thailand. It investigates the strength of linkages from the usage behavior of internet broadband to the goals of the production of creative products and the adjustment of organization that facilitates the production, via the applications of the making the digital database and analysing the data. It uses the structural equation model (SEM) to model this multi-layer relationship. The data are collected from field survey of 400 Small and Medium Enterprises (SMEs). The results reveal that the usage of internet broadband for communication is crucial for the production of creative products. It also discovers that the digital database is important for the modification of organization structure. The digital database is based on the usage of internet broadband in marketing research, searching for contents and collects transactional data of clients. These paths leads to a huge opportunity formobile broadband technology to enhance the creative economy when the functions for communication, searching for contents and marketing research can be done conveniently by mobile devices.